Exploring application portfolio management in Indonesia: A case study of the Indonesia agency for the assessment and application of technology - Riri Kusumarani; Raden Putri Ayu Pramesti (Institute of Advanced Engineering and Science, 2023)
Due to rapid information and communication technology (ICT) growth, government agencies must manage more digital apps to support public service operations and administration. In Indonesia, at least 400,000 applications have been received by various ministries and government agencies. This amount will hurt the ICT budget’s investment and waste if no approach is employed. Problems can be solved with application portfolio management (APM). Indonesian government agencies’ AMP implementation is unclear. APM is applied at the government research institute agency for the assessment and application of technology (BPPT) in this study. BPPT was chosen due to APM’s lack of ICT investment management. This research examined 41 submissions from the 2019 digital transformation initiative. APM selected two mapping models. The outcome indicates how APM may offer ICT strategies for current applications to government entities. This analysis mapped existing applications into two models: McFarlan’s strategic grid and gartner’s TIME model. Mapping findings from these two models-technical health evaluations and regulatory compliance-may be used for application sustainability suggestions. 11 treatments were advised for maintenance and investment, while 4 applications were recommended for removal. This research helps us understand how the Indonesian government institute maintains its application portfolio and how APM might be a valuable method for application management.